Comparação na percepção e aplicação de teste de software entre academia e indústria - Dalto, Vanice (2025)
Context: With the advancement of technologies, new testing methods and tools emerge that require continuous updating of knowledge. This progress, often driven by the industry, can lead to a mismatch between the knowledge traditionally taught in academia and the skills demanded in the market. Therefore, it is essential for testing professionals to not only understand fundamental concepts but also be familiar with emerging technologies and industry best practices, ensuring that testing processes keep up with innovations in software development. Problem: The difference in perception regarding the importance of software testing practices and technologies between academia and industry constitutes a significant problem. This disparity, evidenced in the data analyzed and previous studies, directly impacts how professionals develop skills in the field and influences the costs associated with software quality assurance processes, creating a misalignment between academic training and the real demands of the market. Objective: To verify the perceptions of academics and Information Technology (IT) professionals regarding software testing activities, their concepts, and technologies. Method: This study conducted a survey with academics and IT professionals to identify their views on the subject of software testing, analyzing similarities and differences between these groups. Both groups identified their academic background, while professionals indicated their years of experience and position. Participants answered questions about their level of knowledge in software testing. whether they had a specific course on the subject, the degree of importance of software testing concepts/technologies, among others. Results and conclusion: The data collected from the questionnaires allowed us to identify the software testing activities that each group considers most important, revealing a significant difference in the prioritization and level of knowledge about the practices and techniques analyzed. Academics consistently show lower scores in all categories, indicating less adoption or practical use of these tools and methods. On the other hand, Education Professionals and IT Professionals display higher averages, with greater emphasis on practices related to test automation, integration, and continuous delivery, as well as system and integration testing. These results suggest that the professional market places greater value on these practices than the academic environment, possibly due to their direct application in software development within business settings. The closer alignment between Education and IT Professionals reflects the effort to develop curricula that meet market demands.